Microwave measurements - Collier, R. J.; Skinner, A. D. (Institution of Engineering and Technology, 2007)
The book covers the following areas: microwave measurement.
"Contains most of the lecture notes used during the 14th IET Training Course on Microwave Measurement in May 2005 ... at the National Physical Laboratory in Teddington"--Pref.
Previous ed.: London : Peter Peregrinus, 1989.
Keywords: Microwave measurements -- Congresses.; elektronické knihy; electronic books